The Personal is Political: A Feminist and Trauma-Informed Therapeutic Approach to Working With a Survivor of Sexual Assault. (December 2013) - Richmond, Kate; Geiger, Elizabeth; Reed, Carly
The following case study highlights the application of a conceptual framework that incorporates feminist theory, trauma theory, and the importance of attending to identity development with individuals who have experienced gender-based violence. This case study illustrates the treatment of a 25-year-old female survivor of sexual assault suffering from depression, anxiety, and feelings of self-blame. Findings show a decrease in depression and anxiety, which provides support for the effectiveness of an integrated feminist and trauma-informed therapeutic approach. Because very few graduate training programs incorporate feminist theory and trauma theory in their curricula, recommendations for clinicians and students are provided.